Seeing and feeling volumes: The influence of shape on volume perception - Kahrimanovic, Mirela; Bergmann Tiest, Wouter M.; Kappers, Astrid M.L. (Acta psychologica, 2010)
The volume of common objects can be perceived visually, haptically or by a combination of both senses. The present study shows large effects of the object's shape on volume perception within all these modalities, with an average bias of 36%. In all conditions, the volume of a tetrahedron was overestimated compared to that of a cube or a sphere, and the volume of a cube was overestimated compared to that of a sphere. Additional analyses revealed that the biases could be explained by the dependence of the volume judgment on different geometric properties. During visual volume perception, the strategies depended on the objects that were compared and they were also subject-dependent. However, analysis of the haptic and bimodal data showed more consistent results and revealed that surface area of the stimuli influenced haptic as well as bimodal volume perception. This suggests that bimodal volume perception is more influenced by haptic input than by visual information.